Making Livelihood through Tilapia Farming in Countries like Ethiopia: Making Livelihood through Tilapia Farming in Countries like Ethiopia - Delilo, Gizachew (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2021)
Fish are popular sources of high-quality nutrients such as protein and white meat in many parts of East Africa. However, the gap between supply and demand for fish is expanding. Almost all natural fish stocks in the region, as usual to the world, become overexploited yet human populations and hence demands continue to increase. To establish and run a small-scale fish farm it needs: Labor, land, machetes (pangas), hoes, shovels, pickaxes and wheelbarrows, measuring tapes, wooden pegs, string, lime, fingerlings, fertilizer, weighing scale, and scoop nets. Fish (tilapia) grow best and mature fast when the water temperature is between 25 and 28Â°C. Record keeping helps fish producers to track the major activities undertaken from the start of fish farming business. Keeping simple records of costs and income from sales will allow you to work out whether your fish farming business is profitable.